2009
DOI: 10.1002/ange.200806332
|View full text |Cite
|
Sign up to set email alerts
|

Bindungsmuster zweier C90‐Isomere, bestimmt durch Strukturaufklärung von C90Cl32

Abstract: Seit der Entdeckung der Fullerene C 60 und C 70 sind die Isolierung und Charakterisierung der stabilen Isomere höherer Fullerene ein bedeutendes Forschungsgebiet. Wegen des sehr geringen Gehalts an höheren Fullerenen im fullerenhaltigen Ruß sind allerdings vielstufige HPLC-Verfahren für ihre Abtrennung nötig. Ihre (allerdings nicht immer eindeutige) Charakterisierung erfolgt üblicherweise 13 C-NMR-spektroskopisch, unterstützt durch Berechnungen ihrer relativen Stabilität.[1] Eine weitere Methode zur Charakteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
11
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…[15,16] To further compare D 5h (1)-C 90 with C 70 , we examined the pyramidalization (POAV) angles for the carbon atoms in these fullerenes. [17] For C 60 , the POAV angle is 11.64 (10). [17] For D 5h (1)-C 90 , the POAV angles are: a, 11.91(8); b, 11.95(9); c, 11.70(15); d, 10.37 (19); e, 7.2(2); f, 5.51(15)8; the corresponding angles for C 70 are: a, 11.87(9); b, 12.01(9); c, 11.44 (16); d, 10.18 (17); e, 8.66(16)8.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[15,16] To further compare D 5h (1)-C 90 with C 70 , we examined the pyramidalization (POAV) angles for the carbon atoms in these fullerenes. [17] For C 60 , the POAV angle is 11.64 (10). [17] For D 5h (1)-C 90 , the POAV angles are: a, 11.91(8); b, 11.95(9); c, 11.70(15); d, 10.37 (19); e, 7.2(2); f, 5.51(15)8; the corresponding angles for C 70 are: a, 11.87(9); b, 12.01(9); c, 11.44 (16); d, 10.18 (17); e, 8.66(16)8.…”
Section: Methodsmentioning
confidence: 99%
“…The 13 C NMR spectroscopic studies of Achiba et al [3] produced no evidence for the presence of D 5h (1)-C 90 in their samples, and the products obtained upon functionalization did not reveal the presence of the D 5h isomer either. [9,10] It has been reported that the incorporation of metal salts in the graphite rods used in the electric-arc synthesis can change the composition of fullerenes formed. For example, the addition of gadolinium to the graphite electrodes led to the isolation of isomers D 3d -C 84 and D 6h -C 84 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, triple Cl···Cl contacts in fullerene chlorides destabilize the whole molecule; they are absent even in more overcrowded chlorinated molecules such as C 76 Cl 34 , [10] and C 90 Cl 32 . [11] Notably, so far triple Cl···Cl contacts were found in only one case, C 78 (1)Cl 30 . [12] The addition pattern in C s -C 88 (17)Cl 22 with a chain attachment on one pole and more distant attachment on the second pole closely resembles that seen in C 76 Cl 18 [9a] or C 76 Cl 24 .…”
mentioning
confidence: 98%